THE USE OF JIGSAW TECHNIQUE IN TEACHING READING COMPREHENSION - Anatha, Yudhit (2014)
Teaching reading by using jigsaw technique that introduced by Aronson (1978) was conducted in one junior high schools in Sumedang to investigate whether or not jigsaw technique is effective in improving students' reading comprehension. Brown' (2001:306) presents that reading comprehension is a matter of developing appropriate and efficient comprehension strategies for most second language learners. It shows that to comprehend the texts easily, a reading strategy by applying an appropriate teaching technique is needed; jigsaw technique. Second aim was finding out the students' responses toward jigsaw technique. Employing one group pretest-posttest of pre-experimental design, the data obtained from pretest, posttest, observation and interview were analyzed using paired sample t-test on SPSS 19 for Windows. The findings showed that there was a significant difference between the pretest-posttest results. As indicated by the statistical result of pretest scores (M=58.75) and posttest scores (M=68.25). Furthermore, the result of paired sample t-test showed that tobt (3.005) is higher than tcrit (2.021). By conducting jigsaw technique, the students were not only getting a better score but also they got an enjoyable learning activity in the classroom, building their comprehension to the texts, cooperation and communication skill with their peers and problem solving skills. According to the findings, it can be concluded that jigsaw technique is recommended as an alternative technique in teaching reading comprehension and effective in improving students' reading comprehension. Keywords: jigsaw, technique, reading comprehension Pengajaran membaca dengan menggunakan teknik jigsaw yang diperkenalkan oleh Aronson (1978) dilakukan di sebuah sekolah menengah pertama di Sumedang. Hal ini ditujukan untuk menginvestigasi apakah teknik jigsaw efektif dalam meningkatkan pemahaman membaca pada siswa atau tidak. Seperti yang disampaikan oleh Brown (2001:306) bahwa pemahaman membaca berkaitan dengan pengembangan strategi pemahaman yang sesuai dan efisien bagi kebanyakan pembelajar bahasa kedua. Hal ini menunjukan bahwa untuk memahami sebuah teks dengan mudah dibutuhkan strategi membaca dengan menggunakan teknik mengajar yang sesuai, yaitu teknik jigsaw. Tujuan yang kedua adalah mencari tahu respon siswa terhadap teknik jigsaw. Dengan menggunakan model one group pretest-posttest pre-experimental, data yang diperoleh dari pretest, posttest dan wawancara dianalisis dengan menggunakan paired sample t-test dengan SPSS 19 untuk Windows. Hasil temuannya menunjukan bahwa terdapat perbedaan yang signifikan antara hasil pretest dan posttest. Seperti yang ditunjukan oleh hasil statistik nilai pretest (M=58.75) dan nilai posttest (M=68.25). Kemudian, hasil dari paired sample t-test menunjukan bahwa tobt (3.005) lebih tinggi dari tcrit (2.021). Dengan menggunakan teknik jigsaw, para siswa tidak hanya mendapatkan nilai yang lebih baik tetapi mereka juga mendapatkan kegiatan pembelajaran yang menyenangkan di kelas, membangun pemahaman terhadap teks, kerjasama dan kemampuan komunikasi dengan teman mereka dan kemampuan menyelesaikan masalah. Berdasarkan hasil temuan, dapat disimpulkan bahwa teknik jigsaw direkomendasikan sebagai teknik alternatif dalam pengajaran pemahaman membaca dan efektif dalam meningkatkan pemahaman membaca siswa. Keywords: jigsaw, teknik, pemahaman membaca